Management of Juvenile Temporo-mandibular Joint Ankylosis by Gap Arthoplasty - S Mahmud Mishu; Md Nazmul Hasan; Ali Hossain; Shahiqul Jabbar (Update Dental College, 2014)
Bony ankylosis of the temporomandibular joint (TMJ) in a male patient was not diagnosed until the patient reached his early teens, at which time the condition was treated with a costochondral graft. At the time of treatment, there was an expectation that further orthognathic surgery would be required to correct the skeletal deformity. However, with the release of the ankylosis and growth of the costochondral graft, a good functional and esthetic result was achieved without further surgery. It is important that family dentists be aware of the clinical signs and symptoms of TMJ ankylosis, to allow early diagnosis and treatment. DOI: http://dx.doi.org/10.3329/updcj.v4i1.21172 Update Dent. Coll. j: 2014; 4 (1): 44-48